THE ROLE OF DATA ANALYTICS IN CONTEMPORARY ART MARKET - Khurana, Saniya; Rampal, Sourav; Arguelles, Pastor R.; S. Simonthomas; Pasha, Afroz; Devi, Mona (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Data analytics implementation into the modern art market has changed the way the stakeholders analyze, invest, and interact with art pieces. The art market, traditionally opaque and subjectively valued, is currently adopting data-driven approaches to increase transparency and efficacy, as well as, decision-making. This essay examines the primary importance of the data analytics in transforming the art ecosystem with an emphasis on its uses, advantages, and difficulties. It starts with defining the key elements and classes of analytics: descriptive, predictive, and prescriptive and the technological tools used: artificial intelligence, big data platforms, machine learning algorithms. The tools are then placed in the framework of the art market and discussed on how they can solve the inefficiencies of pricing, valuation, and demand forecasting. Case study examples show how analytics can be used to identify the rising artists, identify the market trends, and prevent fraud risks and manipulation. Alongside these benefits, the paper also mentions such limitations as the lack of data, ethical concerns, and algorithmic bias. Lastly, it also looks into the future opportunities which include blockchain integration, value of digital art and analytics of non-fungible tokens (NFTs). In general, this paper highlights the fact that data analytics is not just democratizing the art investment, but also reshaping cultural and economic value in the ever more digital marketplace.